BEGINNING OF CRIMINAL OFFENSE IN EUROCONTINENTAL AND ANGLOSAXON CRIMINAL LAW - Vasiljević, Dragana (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2022)
Clear and precise definition of the activity that marks the beginning of the commission of a criminal offense, as the boundary between the fundamentally unpunished and the punishable stage of its realization, is of great importance for criminal law. Modern criminal legislation and the doctrine of criminal law are guided by different criteria in determining this boundary. In the Eurocontinental legal system, the definition of criminal attempt is found in theories, while criminal legislation in the Anglo-Saxon criminal justice system in its casuistry rely more on appropriate tests. The article analyzes the theoretical and legislative solutions of the beginning of the commission of a criminal offense and its delimitation from the stage of preparation in Eurocontinental and Anglo-Saxon criminal law.
Keywords: criminal attempt; criminal offense; preparatory actions; Eurocontinental criminal law; Anglo-Saxon criminal law